A qualitative study on the caregiver burden experience in home reflux enema management of infants with congenital megacolon - Yuanyuan Fang; Yulan Kang; Lingjing Teng; Lifang Lin; Pingping Qiu (International Journal of Qualitative Studies on Health & Well-Being)
Objective This study aims to explore the caregiver burden experience in the care of infants with congenital megacolon undergoing home reflux enema. The findings will provide a basis for developing targeted and effective nursing interventions. Methods A phenomenological research approach was employed. From October 2022 to January 2023, semi-structured in-depth interviews were conducted with 12 caregivers of infants with congenital megacolon undergoing home reflux enema in a tertiary paediatric hospital in Fujian Province. The collected data were analysed and organized using the Colaizzi’s 7-step analysis method, leading to the identification of key themes. Results The analysis yielded three major themes concerning the caregiver burden experience in the care of infants with congenital megacolon undergoing home reflux enema: inadequate disease-related knowledge, presence of multiple pressures during the caregiving process, and a desire for greater support. Conclusions This study employed qualitative interviews with the caregivers of 12 children with congenital Hirschsprung’s disease undergoing home reflux enema, and the feelings of caregivers of children with reflux enema at home after discharge were deeply understood. It is recommended to implement positive psychological interventions based on the PERMA model and incorporate “Internet + collaborative nursing” to provide caregivers with professional knowledge, address their pressures and needs, and promote their well-being while enhancing nursing abilities.